The risk-taking channel of liquidity regulations and monetary policy - Stephan Imhof; Cyril Monnet; Shengxing Zhang (University of Bern, Department of Economics, 2018)
We study the implications of liquidity regulations and monetary policy on depositmaking and risk-taking. Banks give risky loans by creating deposits that firms use to pay suppliers. Firms and banks can take more or less risk. In equilibrium, higher liquidity requirements always lower risk at the cost of lower investment. Nevertheless, a positive liquidity requirement is always optimal. Monetary conditions affect the optimal size of liquidity requirements, and the optimal size is countercyclical. It is only optimal to impose a 100% liquidity requirement when the nominal interest rate is sufficiently low.
Keywords: 330